Pembangunan Sistem Informasi Pengelolaan Data Transaksi Bagian Tambang PT. Yasiga Sarana Utama Berbasis Web dengan Fitur Mobile - Rahmi Prisalia; Difana Meilani; Hasdi Putra; Husnil Kamil (Jurnal Nasional Teknologi dan Sistem Informasi, 2015)
Web-based management information system of transaction data with mobile features was needed by employees of PT. Yasiga Sarana Utama, especially mine division. The problems that frequently occur are some documents are created with the manual method, data storage is conducted using Microsoft Excel and duplication. Damage and loss of data have been solved with Web-based management information system of transaction data. In addition, the field employees who have activities outside of the Office get ease in storing and archiving the data using a mobile application integrated with transaction data management information systems. Management information system of transaction data was built using the waterfall method which consisted of the analysis, design, coding or implementing, and testing. In the early stages of development, the company business processes were studied through literatures, and then the company requirements were analyzed using use case diagrams, class diagrams, sequence diagrams, state chart diagrams, and user interface design. The next phase was the design of the system by designing a database using the ER-diagrams. Programming code on the implementation phase was conducted using PHP PDO with object-oriented programming, Bootstrap PostgreSQL database as an additional aesthetic applications, and PhoneGap to generate mobile applications. Application testing was conducted using black box testing. The results of the implementation showed the expected output and in accordance with existing business processes.Keywords—Management Information System of Transaction Data, PT. Yasiga Sarana Utama, Mobile, Waterfall